Improving Student Learning Outcomes with the Two Stay Two Stray Cooperative Learning Model and Flip Chart Media - Nurdin, Syahidan (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to describe the activities of teachers and students, as well as improving student learning outcomes through the use of the cooperative learning model type two stay two stray assisted by flip chart media in learning Citizenship Education in class V MIN 7 Aceh Barat Daya. The type of research used is Classroom Action Research. Data collection techniques using observation and tests. The results of the study found through the teacher activity observation sheet, namely in cycle I reaching 75.02% and increasing in cycle II 95.02%. The results of the student activity sheet, namely in cycle I 73.06% and increasing in cycle II 88.0% with a very good category. Student learning outcomes in cycle I reached 47.22% cycle II increased 85.55% with a very good category. Based on the results of the study, it shows that the application of the cooperative learning model type two stay two stray assisted by flip chart media in Civics lessons can improve student learning outcomes.